2014
DOI: 10.1352/1934-9556-52.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations of Adults With Intellectual Disability in Academic Medical Centers

Abstract: Individuals with intellectual disability (ID) represent a small but important group of hospitalized patients who often have complex health care needs. Individuals with ID experience high rates of hospitalization for ambulatory-sensitive conditions and high rates of hospitalizations in general, even when in formal community care systems; however, no research was found on the common reasons for which this population is hospitalized. Academic medical centers often treat the most complex patients, and data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…8 There have been 3 other large-scale studies on hospitalizations of intellectually disabled adults, but they were unable to differentiate between emergency and planned admissions. 9,20,21 Our focus on preventable emergency admissions means that any comparison is difficult, as we would not expect good primary care management to decrease planned admissions for ACSCs.…”
Section: Contextmentioning
confidence: 99%
“…8 There have been 3 other large-scale studies on hospitalizations of intellectually disabled adults, but they were unable to differentiate between emergency and planned admissions. 9,20,21 Our focus on preventable emergency admissions means that any comparison is difficult, as we would not expect good primary care management to decrease planned admissions for ACSCs.…”
Section: Contextmentioning
confidence: 99%
“…Regarding the second research question, Table summarizes the three studies that consider an overview on whether people with intellectual disabilities are admitted for the same reasons as the general population (Ailey, Johnson, Fogg, & Friese, ; Morgan et al., ; Williams et al., ). Two studies focussed on adults, and one on children up to age 5.…”
Section: Resultsmentioning
confidence: 99%
“…The more methodologically robust of the two adult papers reported that adults are more likely to be admitted for medical and dental reasons, and less likely for surgical reasons (Morgan et al., ). The other adult study did not report data in a comparable way, including only the five most common discharge diagnoses, all of which were medical reasons, and mostly more common in the group with intellectual disabilities (Ailey et al., ). Children with intellectual disabilities were more likely to be admitted than were the comparison group for numerous medical reasons, but not so for disorders of the oral cavity.…”
Section: Resultsmentioning
confidence: 99%
“…There are three other large-scale studies [139][140][141] on hospitalisations of adults with ID that we are aware of, but none differentiated between emergency and planned admissions. Our focus on preventable emergency admissions means that any comparison is difficult, as we would not expect good primary care management to decrease planned admissions for ACSCs.…”
Section: Mortalitymentioning
confidence: 99%